Gain-of-function FHF1 mutation causes early-onset epileptic encephalopathy with cerebellar atrophy. (7th June 2016) - Siekierska, Aleksandra; Isrie, Mala; Liu, Yue; Scheldeman, Chloë; Vanthillo, Niels; Lagae, Lieven; de Witte, Peter A.M.; Van Esch, Hilde; Goldfarb, Mitchell; Buyse, Gunnar M.
Abstract : Objective: Voltage-gated sodium channel (Nav )–encoding genes are among early-onset epileptic encephalopathies (EOEE) targets, suggesting that other genes encoding Nav –binding proteins, such as fibroblast growth factor homologous factors (FHFs), may also play roles in these disorders. Methods: To identify additional genes for EOEE, we performed whole-exome sequencing in a family quintet with 2 siblings with a lethal disease characterized by EOEE and cerebellar atrophy. The pathogenic nature and functional consequences of the identified sequence alteration were determined by electrophysiologic studies in vitro and in vivo. Results: A de novo heterozygous missense mutation was identified in the FHF1 gene ( FHF1AR114H, FHF1BR52H ) in the 2 affected siblings. The mutant FHF1 proteins had a strong gain-of-function phenotype in transfected Neuro2A cells, enhancing the depolarizing shifts in Nav 1.6 voltage-dependent fast inactivation, predicting increased neuronal excitability. Surprisingly, the gain-of-function effect is predicted to result from weaker interaction of mutant FHF1 with the Nav cytoplasmic tail. Transgenic overexpression of mutant FHF1B in zebrafish larvae enhanced epileptiform discharges, demonstrating the epileptic potential of this FHF1 mutation in the affected children. Conclusions: Our data demonstrate that gain-of-function FHF mutations can cause neurologic disorder, and expand the repertoire of genetic causes ( FHF1 ) and mechanisms (altered Nav gating) underlying EOEE and cerebellar atrophy.